2014
DOI: 10.1056/nejmoa1302097
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis for Patients with Intermediate-Risk Pulmonary Embolism

Abstract: In patients with intermediate-risk pulmonary embolism, fibrinolytic therapy prevented hemodynamic decompensation but increased the risk of major hemorrhage and stroke. (Funded by the Programme Hospitalier de Recherche Clinique in France and others; PEITHO EudraCT number, 2006-005328-18; ClinicalTrials.gov number, NCT00639743.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
979
6
92

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,322 publications
(1,141 citation statements)
references
References 27 publications
20
979
6
92
Order By: Relevance
“…The multicenter, double-blind, randomized, placebo-controlled PEITHO (Pulmonary Embolism Thrombolysis) 10 study has recently revealed that rapid thrombolysis reduces the combination of death from any cause and hemodynamic instability in seven days in patients with RV failure and myocardial injury without circulatory shock and this is mainly due to decreased risk of hemodynamic decompensation in these patients. 10 Therefore, these patients, stratified as intermediate risk, who would only receive treatment with anticoagulants, are also thrombolysis candidates with proven benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The multicenter, double-blind, randomized, placebo-controlled PEITHO (Pulmonary Embolism Thrombolysis) 10 study has recently revealed that rapid thrombolysis reduces the combination of death from any cause and hemodynamic instability in seven days in patients with RV failure and myocardial injury without circulatory shock and this is mainly due to decreased risk of hemodynamic decompensation in these patients. 10 Therefore, these patients, stratified as intermediate risk, who would only receive treatment with anticoagulants, are also thrombolysis candidates with proven benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, this scenario seems unlikely in light of the results of the PEITHO trial [33]. While fibrinolysis reduced the risk of decompensation in hemodynamically stable patients with PE who had RV dysfunction and elevated troponin in this trial, overall mortality did not differ, and the risk-benefit ratio of fibrinolysis was worse in patients aged >75 years [34].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for home treatment or short hospitalisation for patients with a low risk of pulmonary embolism needs to be confirmed in further randomised clinical trials. The need for treatment upgrading for patients at intermediate-high risk of death has been only partially shown by randomised clinical trials, as thrombolytic therapy reduces the rate of in-hospital clinical deterioration but not mortality [24][25][26][27][28][29][30][31].…”
Section: Relationship Between Pathophysiology and Risk Of In-hospitalmentioning
confidence: 99%